Legal Protection of Indonesian Migrant Workers - Hasbuddin Khalid; Ade Savirah (Manunggal Halim Jaya, 2022)
This research aims to understand and know the legal protection procedures of Indonesian Migrant Workers and the obstacles that often occur in the Indonesian Migrant Worker's Protection Agency, Makassar Region. To answer the formulation of problems in this study, using a type of empirical research. This research aims to understand and know the legal protection procedures of Indonesian Migrant Workers and the obstacles that often occur in the Indonesian Migrant Worker's Protection Agency, Makassar Region. To answer the formulation of problems in this study, using a type of empirical research. Based on the results of research comparing Indonesian migrant workers that the legal protection procedures of Indonesian migrant workers were conducted at the BP2MI office before work, during work, and after work. Based on the results of research comparing Indonesian migrant workers that the legal protection procedures of Indonesian migrant workers were conducted at the BP2MI office before work, during work, and after work. The obstacles faced by the Indonesian Migrant Workers Protection Agency are many illegal workers who are difficult to track by the government, touts that are difficult to eliminate, and not serious about the government in protecting Indonesian workers abroad.